2013
DOI: 10.1128/jvi.02304-13
|View full text |Cite
|
Sign up to set email alerts
|

Two Overlapping Regions within the N-Terminal Half of the Herpes Simplex Virus 1 E3 Ubiquitin Ligase ICP0 Facilitate the Degradation and Dissociation of PML and Dissociation of Sp100 from ND10

Abstract: Herpes simplex virus 1 (HSV-1) establishes a lifelong latent infection in sensory neurons and can reactivate from latency under stress conditions. To promote lytic infection, the virus must interact with specific cellular factors to evade the host's antiviral defenses. The HSV-1 E3 ubiquitin ligase, infected cell protein 0 (ICP0), activates transcription of viral genes, in part, by mediating the degradation of certain cellular proteins that play a role in host antiviral mechanisms. One component of the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…10 for reasons of completeness and will not be discussed further here. The RING finger itself has been extensively studied previously, while a recent paper implicates the sequences immediately downstream of the RING finger as also being involved in PML degradation (38). Outside all of these regions, the alignment between the ICP0 proteins of HSV-1, HSV-2, and HVB taken together shows considerably less sequence identity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…10 for reasons of completeness and will not be discussed further here. The RING finger itself has been extensively studied previously, while a recent paper implicates the sequences immediately downstream of the RING finger as also being involved in PML degradation (38). Outside all of these regions, the alignment between the ICP0 proteins of HSV-1, HSV-2, and HVB taken together shows considerably less sequence identity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During HSV-1 infection, viral protein ICP0 induces the degradation of PML, thereby disrupting nuclear domain 10 (ND10) 30 , 31 . It has been uncovered that a portion of the C terminus (amino acids 633 to 767), the nuclear localization signal (NLS) and two overlapping regions within the central N-terminal portion of ICP0 (residues 212 to 311) facilitate its dissociation and degradation of PML 69 . In our study, we also observed decreased expression of PML protein after HSV-1 infection (Figure 5 , Figures S6 -8).…”
Section: Discussionmentioning
confidence: 99%
“…Several ND10 constituent proteins, including PML (promyelocytic leukemia), Sp100 (speckled protein of 100 kDa), hDaxx (human death domain-associated protein 6), and ATRX (alpha thalassemia/mental retardation syndrome X-linked) can limit the replication of an ICP0 null HSV-1 mutant [ 41 , 42 , 43 ]. Upon viral infection, ND10-associated proteins are recruited to the incoming viral genome; however, ICP0’s E3 Ub ligase activity promotes the disruption of ND10 (partially through a C-terminal domain, Figure 1 ) by mediating the proteolysis (directly or indirectly) of PML and Sp100 [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] or dissociating hDaxx and ATRX [ 53 ] from ND10. The disruption of ND10s by ICP0 alleviates the repressive functions of ND10-associated proteins and stimulates viral transcription.…”
Section: Icp0 Counteracts the Intrinsic Antiviral Resistance Of Ndmentioning
confidence: 99%